The Charter and Code of the Ordinances of Yazoo City 170-71 (1908) - (:unkn) unknown (My University, 1906)
Ch. 20, § 293: Any person who carries concealed, in whole or in part, any bowie knife, dirk knife, butcher knife, pistol, brass or metallic knuckles, slungshot, sword, or other deadly weapon of like kind or description, shall be guilty of a misdemeanor, and, on conviction, shall be punished by a fine of not less than twenty-five dollars nor more than one hundred dollars, and all costs, or be imprisoned in the county jail not more than ninety days, or both, in the discretion of the court.
Keywords: CARRY - CONCEALED